2011
DOI: 10.1007/s00198-011-1540-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of forearm strength in postmenopausal women

Abstract: Summary Bone strength at the ultradistal radius, quantified by micro-finite element modeling, can be predicted by variables obtained from high-resolution peripheral quantitative computed tomography scans. The specific formula for this bone strength surrogate (−555.2+8.1×[trabecular vBMD]+19.6×[cortical area]+4.2×[total cross-sectional area]) should be validated and tested in fracture risk assessment. Introduction The purpose of this study was to identify key determinants of ultradistal radius (UDR) strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…We found that total cross‐sectional area, trabecular vBMD, and cortical thickness were the strongest HR‐pQCT‐derived predictors of failure load at both the radius and tibia, with cortical porosity also associated with failure load at the tibia. These HR‐pQCT‐derived predictors of bone strength are similar to those identified in other populations including healthy postmenopausal women, young female athletes, and non‐athletes . Importantly, the predictors of failure load at the radius and tibia were the same in African‐American and white women.…”
Section: Discussionsupporting
confidence: 72%
“…We found that total cross‐sectional area, trabecular vBMD, and cortical thickness were the strongest HR‐pQCT‐derived predictors of failure load at both the radius and tibia, with cortical porosity also associated with failure load at the tibia. These HR‐pQCT‐derived predictors of bone strength are similar to those identified in other populations including healthy postmenopausal women, young female athletes, and non‐athletes . Importantly, the predictors of failure load at the radius and tibia were the same in African‐American and white women.…”
Section: Discussionsupporting
confidence: 72%
“…Data from FEA of HR-pQCT have been reported in studies of postmenopausal women, but these data are not available for young female athletes with amenorrhea compared with EA and non-athletes [18]. Additionally, the contribution of cortical parameters and porosity to strength parameters in this population is not known.…”
Section: Introductionmentioning
confidence: 99%
“…A small study of 72 obese men with metabolic syndrome showed that men with estradiol below the median (43 pmol/L) had lower trabecular number, greater trabecular separation and lower bone volume fraction than men with higher estradiol levels but these comparisons were unadjusted for body weight (41) . A study of postmenopausal women reported positive associations between estradiol and trabecular vBMD, cortical area and estimated strength of the ultra-distal forearm but these associations were not significant in the MV model (42) . Bioavailable testosterone was also related to cortical area in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%